Canadian Library Salaries and Material Quality of Life - Pedersen, Jordan (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2025)
This paper seeks to answer what material quality of life can be expected for someone working in a library in Canada, based on the salaries offered in a data set of three months of job postings on a national job board. The postings were categorized by provincial and municipal location and education level. These data were then compared to census information about the cost of housing in the community where the job was located, to approximate whether the pay was sufficient to provide financial stability, and therefore a good material quality of life.The results of the study show that based on the average of all postings, library workers appear to have a good material quality of life. However, a significant number of individual positions did not provide financial stability. Positions that required an MLIS were more likely to provide a good material quality of life, while positions that required a technician diploma were less likely to do the same.I conducted this analysis with the acknowledgement that library workers exist within communities both in the libraries where we work and in the broader sense of where we live. These contexts have power dynamics, and those who have greater financial stability have a responsibility to advocate for, or stand in solidarity with, other members of the community who have less.